Implementasi Metode Simple Additive Weighting pada Sistem Pendukung Keputusan Penilaian Kinerja Pegawai di Puslitbang Polri - Muhamad Fakhri; Senna Hendrian; Siti Khotijah (Pusat riset dan Inovasi Nasional, 2024)
The National Police Research and Development Center (Puslitbang Polri) is a police institution that operates in the field of research, especially those related to the performance of police and community organizations. Supporting elements in the fields of research, study, implementation and development at the National Police Headquarters level which is under the National Police Chief. In the development process, competent and always motivated Human Resources (HR) are needed, one solution is to create a computerized system to increase employee motivation, namely the best employee assessment decision support system. The process of evaluating the best employees at the National Police Research and Development Center is still carried out conventionally so it is less objective and effective. To overcome this problem, a good system is needed. The aim of this research is to make an assessment of the best employees at the National Police Research and Development Center, because there is no system that can help the Head of the National Police Research and Development Center and the Head of the Human Resources Subdivision to determine the best employee assessment. This research aims to find out the best employees using data from 8 employees at the National Police Research and Development Center. The method used is Simple Addtive Weighting (SAW) with 4 attributes. The results of the research were that 1 was selected as the best employee and received a salary bonus.